Prevalence of self-reported overweight-obesity and its association with socioeconomic and health factors among older Mexican adults Prevalencia de sobrepeso-obesidad autorreportados y su asociación con factores socioeconómicos y de salud en población de edad avanzada en México - Liliana Ruiz-Arregui; Lilia Castillo-Martínez; Arturo Orea-Tejeda; Silvia Mejía-Arango; Alejandro Miguel-Jaimes (Instituto Nacional de Salud Pública, 2007)
OBJECTIVE: To investigate the prevalence of obesity and its association with socioeconomic factors and comorbidities in a population-based study. MATERIAL AND METHODS: Data were examined from 4 605 persons ages 60 and older that participated in the 2001 Mexican Health and Aging Study, conducted in rural and urban communities in Mexico. The prevalence of obesity (according to self-reported weight and height) was obtained, stratified by age, and logistic regression was used to study cross-sectional associations between obesity and socioeconomic factors. RESULTS: Of the population studied, 20.9% were classified as obese and the prevalence diminishes with age. Overall, women were more likely than mentobe obese. Lower educational level was associated with lower risk of overweight. In both men and women, obesity was more common between subjects with hypertension (OR 1.38 and 1.71, respectively) and long-distance walk limitation (OR 2.08 and 2.21, respectively). CONCLUISON: In older Mexican adults, hypertension and long-distance walk limitation were independent associated factors for higher prevalence of obesity. OBJETIVO: Estudiar la prevalencia de obesidad y su asociación con factores socioeconómicos y comorbilidades. MATERIAL Y MÉTODOS: Se analizaron los datos de 4 605 personas de 60 años y más que participaron en el Estudio Nacional sobre Salud y Envejecimiento en México 2001 (ENASEM 2001) en zonas rurales y urbanas. La prevalencia de obesidad (peso y talla autorreportados) se obtuvo estratificada por edad y mediante una regresión logística se asoció con factores socioeconómicos. RESULTADOS: 20.9% se clasificaron como obesos y la prevalencia disminuyó con la edad. En general las mujeres tuvieron mayor probabilidad de ser obesas. Una baja escolaridad se asoció con menor riesgo de sobrepeso. En hombres y mujeres la obesidad se asoció con hipertensión (RM 1.38 y 1.71 respectivamente) y con dificultad para caminar (RM 2.08 y 2.21 respectivamente). CONCLUSIÓN: En la población de edad avanzada en México la hipertensión y la dificultad para caminar varias cuadras se asoció con mayor prevalencia de obesidad.